The prequalified competition - how are architects appointed to invited architectural competitions? - Rönn, Magnus (Enquiry The ARCC Journal for Architectural Research, 2012)
This article presents results from a study of prequalification in architectural competitions. The aim is to develop knowledge of how the organizer appoints candidates to invited competitions. Prequalification is a selection procedure used early in the competition process to identifysuitable candidates for the following design phase. Usually three to six teams are invited to develop design proposals. The overall research question in the study is about how organizers identify architects / design teams for competitions with limited participation. The methodology includes an inventory of competitions, case studies, document review and interviews of key-persons. Ten municipal and governmental competitions have been examined in the study. There are 375 applications from design teams in the competitions. 43 architect firms/teams (11 %) have been invited. In five of the ten competitions 19 informants have reported their experiences of prequalification. The informants responded to an interview guide with questions on the background of the competition, development of the invitation, and the need for information about the candidates, assessment process and experience from the selection of architects / design teams. The invitation emerges during negotiation at the organizing body, which includes discussion with the Swedish Association of Architects.General conditions, submission requirements and criteria for the evaluation of applications by architect firms are part of an established practice. All clients have an assessment procedure made up of two distinct stages. First they check whether applications meet the specific "must requirements” in the invitation. Thereafter follows an evaluative assessment of the candidate's professional profile, which is based on the criteria in the invitation. Reference projects and information from the referees are important sources of information in this stage. Decisivein the final assessment is the organizer's perception of the candidates' ability to produce projects of architectural quality, the ability to combine creative solutions with functional requirements and aptitude to work with developers and contractors.